Trade in health products: Reducing trade barriers for better health - Matthias Helble; Benjamin Shepherd (Asian Development Bank Institute (ADBI), 2017)
Trade in health products has been flourishing in recent years as the demand for better health has been growing throughout the world. At the same time, trade in health products is hampered by substantive trade barriers. In this paper, we present evidence that countries around the world still apply tariffs and nontariff measures that increase prices and limit the availability of health-related products such as pharmaceuticals, vaccines, and medical equipment. The case for liberalizing trade in these products is therefore strong. In addition, we show that improving trade facilitation performance, using the World Trade Organization's Trade Facilitation Agreement as a starting point, can be linked to improved handling of health-related products such as vaccines which, in turn, would boost usage. In the last part of the paper, we study the price differences for insulin across countries. We observe that the price of insulin has various determinants, one of them being open trade: the higher the level of competition between manufacturers, the lower the price of insulin. In summary, lowering trade barriers on health products can make a substantive contribution to building up health systems and lowering out-of-pocket payments of patients.
Keywords: F14; I11; I15; I18; 330; trade; trade barriers; health products; pharmaceuticals; tariffs; non-tariff measures; trade liberalization; WTO Trade Facilitation Agreement; vaccine; insulin